Potential of Secondary Metabolite of Jasminum sambac as Diabetes Mellitus Medicine by Molecular Docking Method - Alghifari, Mochammad Rehan; Jamil, Ahmad Shobrun; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2023)
Diabetes mellitus (DM) is a non-infectious disease with a high prevalence in Indonesia. The study explored the potential of the phytochemical component of Jasminum sambac to treat DM. The potential of Jasminum. sambac as a candidate for DM therapy was demonstrated through in silico analysis using several databases and computer-aided drug discovery tools. The bioactive compounds analyzed were obtained from KnapSACK databases. The screening was done to find compounds by estimating bioavailability prediction on the SwissADME. The SwissTargetPrediction tool connects predictions of target proteins from compounds that pass screening to various probable proteins and utilizes the String-DB to show the network between target proteins and associated diseases. After finding the target protein, continue docking the chemical compound to the target protein using PyRx with AutoDock 4.2.6. The search results for the compounds in Jasminum sambac found nine active substances with good bioavailability. The results of the pharmacological network found four proteins associated with Jasminum sambac , among others: GCGR, GSK3B, PPARA, and PPARG. In addition, in-depth analysis was done on the molecular interactions that occurred, how these compounds bind the enzymes found in humans, and their potential to be inhibitors of diabetes mellitus. Proteins such as GCGR, GSK3B, PPARA, and PPARG bind to the compounds found in Jasminum sambac , such as (-)-alpha-cadinol and linalyl benzoate. Thus, it can be said that Jasminum sambac can have anti-diabetic activity.